Silver/selenium/chitosan co-substituted bioceramic coatings of Ni-Ti alloy: Antibacterial efficiency and cell viability - Say, Yakup; Aksakal, Bunyamin; Sinirlioglu, Zeynep A. (WILEY, 2022)
The effects of silver (Ag), selenium (Se), and chitosan (Cht) additives on the antibacterial activity and cell viability of NiTi were investigated. Three different hydroxyapatite (HA)-based bioceramic coatings to improve the antibacterial activity and cell viability of NiTi; HA, HA/Ag, and HA/Se-Cht were applied to NiTi substrates by a sol-gel method. The coated samples were characterized by scanning electron microscopy-electron-dispersive spectroscopy and X-ray diffraction and surface hardnesses were measured. The antimicrobial efficiency of the coatings and uncoated surfaces were tested against Escherichia coli-JM 103 and Staphylococcus aureus-ATCC29293. In vitro cell-material interactions using Saos-2 osteoblast cells were characterized by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (mitochondrial activity test) assay for cell viability. A homogeneous, crack-free, and porous surface morphology is achieved in coatings. It has been shown that the Se-Cht additives did not have a significant effect on the surface hardness of the HA coating, but the Ag additive increased the hardness. Through in vitro antibacterial activity and cell viability tests, it was shown that Ag additive to bioceramic coatings significantly increased (p < .05) antibacterial properties but caused a decrease in cell viability. However, although Se-Cht additives did not have a significant effect on antibacterial properties (p < .05), it was observed that they increased cell viability.
Keywords: antibacterial activity; cell viability; chitosan; hydroxyapatite; NiTi; selenium; DOPED HYDROXYAPATITE; BIOCOMPOSITE SCAFFOLDS; SURFACE MODIFICATIONS; CORROSION-RESISTANCE; TITANIUM; NANOTUBES; IMPLANT; SILICA; ION; Materials Science